Microbial and chemical risk from reclaimed water use for residential irrigation. Issue 3 (30th July 2022) - Weidhaas, Jennifer; Olsen, McKinley; McLean, Joan E.; Allen, Niel; Ahmadi, Leila; Duodu, Kwame; Dupont, Ryan
Abstract: Arid and semi-arid locations are increasingly utilizing nontraditional irrigation water including reclaimed wastewater. Human health risk associated with reclaimed wastewater use was determined by testing reservoir, distribution line and home spigot water ( n =190) and 14 types of vegetables and fruits ( n =90) harvested from 5 home gardens for 7 waterborne pathogens, 47 antibiotic resistance genes and 12 pharmaceuticals and personal care products (PPCPs). Based on surveys of the residents' use of the reclaimed wastewater, two exposure routes were modeled: irrigation of fruits and vegetables and drinking from irrigation hoses. Probabilistic quantitative microbial risk assessment indicated that consumption of raw vegetables and fruits exceeded a 0.015 benchmark illness rate due to adenovirus and enterococci. Chemical risk assessments indicated that consumption of tons of vegetables per day and hundreds to millions of gallons of water per day would be needed to reach an unacceptable risk among the 10 PPCPs detected in home spigot water, indicating de minimis risk from PPCPs. Eight different drug resistance gene families were detected in the water samples and crops indicating that antibiotic-resistant organisms are present on foods irrigated with reclaimed water containing pharmaceuticals. These results elucidate the combined risk from pathogens and PPCPs from reclaimed wastewater irrigation. HIGHLIGHTS: Reclaimed wastewater irrigation presents unacceptable microbial human health risks. Reclaimed wastewater used for irrigation fosters antibiotic resistance associated with PPCPs. Irrigation with reclaimed wastewater presents de minimis chemical health risk. Pathogens and PPCPs accumulate differentially in vegetable skin and flesh. Graphical Abstract